Literary presentation of the childhood in the European memorials: from the Enlightenment to Romantic (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article deals with the literary presentation of childhood in European memoirs in the ХVIII–ХІХ century issue. The literary concept and separate narrative models of childhood of European authors of the ХVIII–ХІХ century are analyzed. Particular meaning of the childhood issues in works of the romantic period is underlined.
Keywords: autobiography; author; education; childhood; image; conception